"IT'S A DISEASE OF FAMILIES": NEUROLOGISTS' INSIGHTS ON HOW PARKINSON'S DISEASE AFFECTS FAMILY DYNAMICS. (11th November 2018) - Schwartz, R; Zulman, D; Gray, C; Trivedi, R
Abstract: Neurodegenerative disease, such as Parkinson's disease (PD), presents an evolving challenge for patients, caregivers and families. Although patient well being may be dependent upon caregiver and family support, the time constraints of neurology clinic visits limit the degree to which caregiver needs may be addressed. Objective: In this study, we explore neurologists' perspectives on the challenges PD presents for caregivers and families. Methods: We conducted hour-long semi-structured interviews with 16 neurologists at four care delivery institutions in the San Francisco Bay Area, focusing on the strategies neurologists use to assess and negotiate family dynamics relating to PD-induced changes. Results: Four themes emerged: 1) Effects of PD on gender and family dynamics; 2) Strategies for navigating caregiver-patient disagreement around patients' functional abilities; 3) Caregiver and family education needed; and 4) Perceived unmet needs of patients and their families. Neurologists perceived that patient and caregiver challenges differ according to gender. They reported a need for additional support in bridging patient and caregiver perspectives, particularly around symptom distress, threats to independence, and disease-specific challenges that compromise interpersonal communication. Conclusions: Neurologists identified core areas where additional structural support, in the form of respite care, psychosocial support, in the form of counseling, and educational support is needed to improve patient and family quality of life. Through understanding the individual and interpersonal challenges PD poses to caregivers and family members, new strategies for providing support to caregivers and families can be developed to alleviate current burdens and allow for improved patient care.